In different fronts: the daughters of charity and their educational experiences in the Minas Gerais and the Rio de Janeiro (1850-1900) - Aline de Morais Limeira Pasche; Maria Aparecida Arruda (Universidade Federal de Santa Catarina, 2018)
Understanding the importance of reflecting on the articulations between public power and the Catholic Church throughout the development of the schooling process in Brazil, this study aims to investigate educational experiences of religious initiatives of a specific Order in action since the second half of the nineteenth century. In this case, we proposed the analysis of the role of the Daughters of Charity (Order of Saint Vincent de Paul) in the field of Education, based on some world orientations of the Order, whose activity was carried out in several countries. The Statutes of the Order of Saint Vincent de Paul intended to regulate their practices, elaborating a complex system of rules, principles, aims and norms. Thus, we seek to analyze the proposal of religious services, and the representations erected around the educational action, based on the assumptions specified in that document and in the other sources analyzed (commercials, official reports of the teaching administration, printed). Specifically, we intend to inquire about their actions in the provinces of Minas Gerais and Rio de Janeiro. For the purpose of the analysis, two examples of educational institutions created by the Vincentians belonging to the private teaching network were studied: in Minas Gerais, an Externato (with lectures) in the city of São João del Rei; and in the province of Rio de Janeiro, the Immaculate Conception College in the Imperial Court, founded in 1855 (in operation until today). As a result, we perceive that, although geographically distant, the analyzed institutions present more characteristics that approximate them in an effort for the common investment of education.